Changes in the levels of vitamin D receptor and active form of the nuclear factor κB in bone tissue of rats with experimental type 1 diabetes mellitus and their correction with cholecalciferol - Mazanova, A.O.; Shymanskyi, I.O.; Lisakovska, O.O.; Vasylevska, V.M.; Lototska, O.Yu.; Makarova, O.O.; Veliky, M.M. (Reports of the National Academy of Sciences of Ukraine, 2018)
It has been shown that chronic hyperglycemia, caused by the development of experimental type 1 diabetes mellitus (DM 1), leads to a significant decrease in the blood serum level of 25OHD. Vitamin D3 deficiency in rats with DM 1 is accompanied by the impaired signaling of calcitriol in bone tissue, as is evident from a decrease in the expression of the vitamin D3 receptor protein (VDR). The elevated level of nuclear factor κB (NF-κB) subunit p65 phosphorylated at Ser 311 in bone tissue is found. This may contribute to an increase in osteoclastogenesis. Supplementation of cholcalciferol (vitamin D3) to rats with DM 1 leads to a normalization of 25OHD in blood serum, which can result in the restoration of the osteoblastic-osteoclastic balance in bone tissue.